Optimizing root physiology and soil nutrient balance in rice–wheat sequence using polyhalite for enhanced profitability in the Indo-Gangetic plains of India - Kumar, V.; Shekhawat, K.; Rathore, S.S.; Upadhyay, P.K.; Singh, R.K.; Gairola, A.; Sharma, D.; Pandey, A.; Roy, S. (2025)
Excessive application of high-analysis fertilizers disrupts ecosystem balance and raise environmental concerns. Potassium (K) and sulphur (S) are crucial nutrients for plants optimum growth and development. Potassium uptake exceeds nitrogen (N) by almost 1.5. Its deficiency diminishes yield (~ 20%) and compromise stress resilience. Potassium application through MOP observes low recovery, poor nutrient equilibrium, suboptimal monetary returns, and environmental threats. In contrast, polyhalite, a natural multi-nutrient mineral containing K, magnesium (Mg), calcium (Ca), and S, presents promising alternative for mitigating nutrient imbalances, enhancing soil health, and higher farm profitability. A field experiment at ICAR-Indian Agricultural Research Institute, New Delhi, was conducted during rabi 2021–22 to evaluate K sources viz. polyhalite, bentonite, and MOP in optimizing plant growth and nutrient uptake. The grain N content under 100% K (polyhalite) was 4.36, and 1.89% higher over 100% K (MOP), and 100% K (MOP)+ bentonite-S equivalent, respectively. Potassium content in grain and straw was 30.3% and 10.38% higher, respectively, over K supply with sole MOP. The optimal K dose (polyhalite) registered 23% higher root length density, 2.64% higher root volume, and 1.28-folds higher root diameter over 100% (MOP). Polyhalite as a K source offered 1.83 and ~ 2-folds higher agronomic efficiency over 100% K (MOP) and 75% K (MOP), respectively. The greater actual net gain in soil K was observed and recorded with 100% K (polyhalite; 20.1 kg ha−1), followed by 100% K (MOP)+ S-equivalent to T8 (19.1 kg ha−1). A net gain of 2 kg ha−1 in Soil S was registered under polyhalite over MOP application. Across the treatments, 100% K (polyhalite) revealed 1.35 and 1.22-times higher net returns over conventional (100% K-MOP) and blend combination (50:50; MOP+ polyhalite), respectively.